Board Characteristics and Firms' Specific Variables on Capital Structure of Consumer Cyclical and Non-Cyclical Sectors of Shariah-Compliant Firms in Indonesia - Bayuny, Ahmad Fadlur Rahman; R. Moh. Qudsi Fauzi; Sunan Fanani; Fathiya Ni'matul 'Aisy (Airlangga Journal of Innovation Management, 2025)
This study is motivated by the growing importance of understanding capital structure decisions in Sharia-compliant firms, particularly as these firms operate under unique governance mechanisms shaped by Sharia principles and the oversight of the Sharia Supervisory Board. The purpose of this research is to examine how board characteristics and firm-specific factors influence capital structure in Indonesia’s consumer cyclical and non-cyclical Sharia-compliant sectors. Using panel data from 57 firms over the period 2007–2020, this study employs the Generalized Method of Moments (GMM) to analyze the effects of board size, commissioner size, and internal firm variables on leverage decisions. The results indicate that larger boards significantly reduce leverage, and greater commissioner presence is associated with lower reliance on debt, while firm age, tangibility, size, growth opportunities, Tobin’s Q, and profitability also play significant roles in shaping leverage decisions. Based on these findings, firms are encouraged to strengthen governance quality, particularly in board structure and supervisory mechanisms, to achieve more prudent and sustainable capital structure policies aligned with Sharia principles.